Dispute resolution in transnational securities transactions - Andreotti E Silva, Tiago (European University Institute, 2014)
This PhD thesis explores how the legal infrastructure for dispute resolution in transnational securities transactions can be improved, considering the regulatory and legal limits of the financial sector in each jurisdiction under study (US, Europe and Brazil). The two main objectives of the work are to a) identify the problems that currently exist for a dispute resolution mechanism in the securities area that can be used transnationally and b) propose solutions that can create a safe legal environment that can be used by the investor in case regulatory rules or the terms of the transaction are breached. The work is justified by the fact that financial markets are legal constructions, making legal certainty and the mechanisms available to enforce the terms of a transaction and apply regulatory rules, especially to the investor that is part of the transaction, essential for the own existence of financial markets. Therefore, the existence of transnational financial markets also depends on the existence of a transnational legal infrastructure, at least broad enough to protect the interest of investors. The argument developed through the work is that the creation of a transnational legal infrastructure depends on the type of dispute that is considered, since not only each type of dispute has its own peculiarities, but the national dispute resolution systems are also built based on the type of dispute that will be submitted to it. To create transnational dispute resolution systems for securities transactions, I propose the use of collective mechanisms of dispute resolution based on the initiative of private parties, the use of arbitration and the establishment of cooperation networks among national alternative dispute resolution mechanisms used to solve financial disputes.
Keywords: Dispute resolution (Law); Financial market; International finance; Security (Law)